Investigation of the anti-cancer effect of Lamium purpureum on prostate cancer cell lines - (:unkn) unknown (My University, 2022)
Abstract Cancer is the most common and deadly disease in the world after cardiovascular diseases. Human prostate cancer ranks second in incidence worldwide after lung cancer in men. Anticancer, anti-inflammatory, antioxidant, antimicrobial, antiviral and antiobesity effects of some plants are known. The genus Lamium is a herbaceous species in the Lamiaceae family. Antioxidant, antibacterial, antimicrobial, anti-inflammatory, cytotoxicity and antityrosinase activities of the genus Lamium have been shown before. In this study, the anticancer effect of Lamium purpureum, a species belonging to the genus Lamium, was studied in LNCaP androgen-dependent human prostate cancer cell lines. Extracts derived from n-hexane (SSH), aqueous ethanol (SSSE), chloroform (SSK), ethyl acetate (SSEA), maceration ethanol (SSME) prepared from Lamium purpureum plant were used. The cytotoxic effect of the extracts was examined with the CCK-8 kit after 24 and 48 hours of incubation. IC50 values were calculated using the results obtained. Accordingly, the IC50 values for SSH, SSSE, SSK, SSEA, SSME in the LNCaP cell line were 20.33, 86.66, 78.07, 70.41, 27.18 ug/ml for 24 hours; 19.93, 48.81, 35.05, 56.92, 15.35 ug/ml for 48 hours, respectively. The JC-1 mitochondrial membrane potential test was used to determine possible depolarization in the mitochondrial membrane potential. As a result of the 48-hour study with SSH and SSK, no depolarization tendency was observed in the mitochondrial membrane potential. These preliminary results suggest that the extracts suppress cell proliferation by showing cytotoxic effects, but may not stimulate the intrinsic apoptotic pathway. Further studies will be carried out to support the results. This study was supported by Marmara University Scientifical Research Projects Commission with project number TYL-2022-10417. Keywords: Lamium purpureum, LNCaP, prostate cancer, apoptosis, anticancer
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)